Heritage language proficiency in relation to emotional attachment, motivations and attitudes: a comparative study of Malaysian Chinese (Mahua) - Qian, Long; Boon Sim, Ng; Ling Yann, Wong; Abdul Halim, Hazlina (Universiti Putra Malaysia, 2024)
Emotional attachment (EA) to the community's language reshape speakers' identities and aids in maintaining that language language in most immigrant societies. Language also serves the social purpose of identifying identity characteristics and significantly impacts social identity development. However, more research is still needed on how Chinese Heritage Language Learners (CHLLs) form their identities, particularly when examining the relationship between this identity construction and language learning (Zhou, 2016). Therefore, this study uses a quantitative approach to explore the correlations between EA and CHLLs' motivation and and attitudes with Malaysian CHLLs' Chinese Language Proficiency (CLP) in relation to EA, motivations and attitudes. It also draws on the Chinese Identity Theory (Wang, 1985) and Gardner and Lambert's (1972) psychosocial model. The study found that participants in Malaysian public and private schools showed high CLP in listening, speaking and reading (over 80%), relatively low scores in writing (approximately 77%) and with positive attitudes toward learning Chinese, high integrative motivation, and low CHL classroom anxiety; the distinction is that, while Chinese cultural identity and attitudes toward Malaysian Chinese are thought to be the best predictors of CLP for the public school group, traditional costume, Chinese cuisine, Chinese architecture etc are considered the best predictors of CLP for the private school group.